(untitled) (Research, Society and Development, 2022)
Objective: to analyze the production of knowledge, in the Brazilian context, on the evidence related to the potentiating and limiting factors recognized by health professionals about the identification and maintenance of the potential donor of organs and tissues in brain death and to identify proposals for interventions to improve this process. Methodology: This is an integrative literature review, developed in the LILACS, BDENF and SCIELO library databases, from April to June 2020. Results: The review corpus consisted of 35 articles, and after analysis, the technical-scientific competence of the professionals, the integration of the multiprofessional team, awareness, mobilization and sensitization of the teams for care were identified as potentiating factors. As limiting factors, insecurity, inexperience, lack of knowledge, technical and emotional unpreparedness, absence of protocols or guidelines, deficiencies in physical, material, technological and human resources, lack of professional, personal and emotional maturity, and lack of a giving culture. Permanent education was defined as the main intervention strategy to optimize the process. Conclusion: The importance of knowledge that professionals have on the subject, teamwork and understanding of the meaning of their participation in this process, as well as permanent health education strategies in the hospital environment are necessary to improve the quality of care provided to the patient. potential brain-dead organ donor.